(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
This present experimental work investigates the influence of nanoparticles added to biodiesel blend on the engine performance and emission characteristics. The nanofuel is prepared by adding the aluminum oxide (Al2O3) nanoparticle to biodiesel – diesel blend and compared with pure diesel and biodiesel –diesel blend. The effect of 25 ppm , 50 ppm , and 100 ppm of aluminum oxide( Al2O3) nanoparticles with size 25 nm , added to biodiesel blend are experimentally investigated in a diesel engine type( FIAT), four cylinder ,direct injection (DI), water cooled , and compression ratio 17 :1. with variable engine speed and load . The aluminum oxide was mixed with (BIO20%+DIESEL 80%) B20 fuel blend by the aid of ultrasonicator technique. The nanoparticles adding to B20 improved and increased the physical properties of nanofeul such as cetane number , calorific value , density , flash and fire point and viscosity. Improvement in engine performance is very clear with nanoparticles additives, the specific fuel consumption decreases by 15.5% for 25 ppm, 10.4% for 50 ppm and 6.13% for 100 ppm as compared with neat B20 at full load and all operation condition. The brake thermal efficiency increased by 20.8% for 25 ppm, 17.4 % for 50 ppm and 4% for 100 ppm as compared with neat B20 at full load and all operation condition. The exhaust temperature is reduced by 18.19 % for 25ppm , 17.15% for 50 ppm and 13.17% for 100 ppm .The emission results at all loads show a reduction of the (UHC) , (NO X ) and (CO) emission by 15.6% , 16% and 18.18% respectively for 25 ppm .